If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10.3x + 1 = 2x + 4 Reorder the terms: 1 + 10.3x = 2x + 4 Reorder the terms: 1 + 10.3x = 4 + 2x Solving 1 + 10.3x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 1 + 10.3x + -2x = 4 + 2x + -2x Combine like terms: 10.3x + -2x = 8.3x 1 + 8.3x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 1 + 8.3x = 4 + 0 1 + 8.3x = 4 Add '-1' to each side of the equation. 1 + -1 + 8.3x = 4 + -1 Combine like terms: 1 + -1 = 0 0 + 8.3x = 4 + -1 8.3x = 4 + -1 Combine like terms: 4 + -1 = 3 8.3x = 3 Divide each side by '8.3'. x = 0.3614457831 Simplifying x = 0.3614457831
| 2lnx-ln(2x-7)=ln(9x)-ln(x-2) | | -14k^2-280=0 | | 3z-1z+2z-30=70 | | x+10=-100 | | 9x+10=8+8x | | 5/(x-4)=0 | | -2(2x-5)=2(X-7) | | 3y-1z+2z-30=70 | | -10x^2+22x+12=0 | | 13=p-(-15) | | 5x(4-x)=9-(x-6) | | -10y-5y=120 | | 2cos(0.5)-1=0 | | 7=b+2 | | r^2-10x-50=0 | | -6x-1x=56 | | -4/4=x | | 96x-9/2x^2 | | 2x^2-7x-16=0 | | Z-br=pforb | | 7+5k=-13+2k-2k | | 3x+4=5x+10-2x | | 3.6−2.5(4.8÷1/2)= | | 2*1.2-y=2 | | 5x+5=-6x+2 | | 3.6−2.5(4.8÷1/2) | | 15x-10x=5x | | 15x-10x=5x | | Z-br=p | | 15x-10x=5x | | 8x^3-5x=0 | | 15x-10x=5x |